1968
DOI: 10.1002/macp.1968.021170105
|View full text |Cite
|
Sign up to set email alerts
|

Polymerisation of acrylonitrile by V5+/cyclohexanol‐redox system

Abstract: The effects of the concentrations of monomer, cyclohexanol, V5+, H,SO,, HSO,, SO:-, Cland ionic strength a t 40 to 6OoC on the rate of V5f disappearance and the rate of polymerisation of acrylonitrile were studied. From the experimental results, it was concluded that the organic free radicals formed during the decomposition of the V5f-cyclohexanol complex, initiated polymerisation and that the polymer radicals were terminated by V5+ ion. An appropriate kinetic scheme was proposed and the various rate and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…39 Lot of work has been done on the kinetic studies of vinyl polymerization using V(V) -organic substrates as redox systems. [40][41][42][43][44] The presMethod ent piece of work deals mainly with polymerization of methyl acrylate (MA) initiated by a V(V)-…”
Section: Introductionmentioning
confidence: 99%
“…39 Lot of work has been done on the kinetic studies of vinyl polymerization using V(V) -organic substrates as redox systems. [40][41][42][43][44] The presMethod ent piece of work deals mainly with polymerization of methyl acrylate (MA) initiated by a V(V)-…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies 7,38,39 have indicated that the form of the active vanadium(V) species depends on acid types and their concentration range. It has been established by the earlier workers 7,38,39 that in aqueous sulfuric acid media (⩽4.5 mol dm −3 ) the kinetically active species of vanadium(V) is [V(OH) 3 HSO 4 ] + and the equilibrium leading to this active species is given by 7,38–41 In the same way, the results obtained in higher acid concentration range (>4.5 mol dm −3 ), the following equilibria can be considered to be operative 42 for the formation of the active species in this range: The result can be explained by considering the proposed mechanism (Scheme ) The pseudo‐first‐order rate constants ( k obs ) in the presence of various concentrations of different types of surfactants, SDS (sodium dodecyl sulfate, a representative anionic surfactant), CPC ( N ‐cetylpyridinium chloride, a representative cationic surfactant), and TX‐100 (Trion X‐100, a neutral surfactant), are presented in Table I.…”
Section: Resultsmentioning
confidence: 72%
“…A plot of the reciprocal of R p (obs) versus the Cr(VI) concentration is linear (Fig. 3), indicating linear termination 20 . R Cr also increased with an increasing Cr(VI) concentration in the presence of 0.015 M SDS.…”
Section: Resultsmentioning
confidence: 93%